2004
DOI: 10.4103/0019-509x.12347
|View full text |Cite
|
Sign up to set email alerts
|

Premalignant lesions of prostate and their association with nodular hyperplasia and carcinoma prostate

Abstract: BACKGROUND:A relatively new development in the arena of prostatic histopathological study is the premalignant proliferative changes in the glandular epithelium, possibly relating to carcinoma. Two major categories have come up, namely prostatic intraepithelial neoplasia (PIN) and atypical adenomatous hyperplasia (AAH). AIMS: The aims of present study were to identify foci of the two putative premalignant conditions viz. PIN and AAH in ducto-acinar lining epithelia of 200 prostatectomy specimens and their assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…[6][7][8][9][10] In studies done by Kumaresan et al 4 and Shah RB et al, 11 the incidence of BPH with suspicious focus ranged from 26 -46%; in our study we found an incidence of 30%. Premalignant lesions like LGPIN and HGPIN in the present study had an incidence of 13.3% and 10% respectively which is similar to studies done by Rekhi et al 12 (11.2%) and Kumaresan et al8 (14.2%). The incidence of Prostate Adenocarcinoma was comparable to studies by Jasani et al, 13 Haroun et al, 14 Xie et al 9 and Shimada et al 10 A correlation between serum PSA levels and histopathological diagnosis was done in the present study which showed all the lesions have a raised (>4ng/mL) PSA levels with mean PSA value being higher in the Prostate Adenocarcinoma patients as compared to BPH and other pre-malignant entities.…”
Section: Discussionsupporting
confidence: 91%
“…[6][7][8][9][10] In studies done by Kumaresan et al 4 and Shah RB et al, 11 the incidence of BPH with suspicious focus ranged from 26 -46%; in our study we found an incidence of 30%. Premalignant lesions like LGPIN and HGPIN in the present study had an incidence of 13.3% and 10% respectively which is similar to studies done by Rekhi et al 12 (11.2%) and Kumaresan et al8 (14.2%). The incidence of Prostate Adenocarcinoma was comparable to studies by Jasani et al, 13 Haroun et al, 14 Xie et al 9 and Shimada et al 10 A correlation between serum PSA levels and histopathological diagnosis was done in the present study which showed all the lesions have a raised (>4ng/mL) PSA levels with mean PSA value being higher in the Prostate Adenocarcinoma patients as compared to BPH and other pre-malignant entities.…”
Section: Discussionsupporting
confidence: 91%
“…The toxic effect of Tacrolimus that appear in histopathological sections in liver may be due to the accumulations of active metabolits of Tacrolimus for long time as a result of repeated exposure for 90 days, as well as the long half live of drug (36 hrs.). Hyperplasia is multi proliferations of cells its considered precancerous lesions (31). The results indicated that the free radical that generated from the inhibition of the nitric oxide synthetas by Tacrolimus (32).…”
Section: Subcapsularmentioning
confidence: 97%
“…Prostate cancer is responsible for 3% of all deaths in men above 55 years of age [5] . A relatively new development in the prostatic histopathology is the identification of premalignant conditions that can help in early diagnosis of prostate cancer [6] . A combination of digital rectal examination, transrectal ultrasonogram and needle biopsy can prove to be a powerful diagnostic tool in the routine diagnosis of benign and malignant prostatic lesions [7] .…”
Section: Introductionmentioning
confidence: 99%